Exploring the transition from heterotrophy to high light stress using a proteomic and phosphoproteomic approach reveals altered chlorophyll biosynthesis, carbon partitioning, and astaxanthin biosynthesis and trafficking in a Haematococcus pluvialis (Chlorophyceae) mutant - Kyarii Ramarui; Jie Wang; Gary H. Wikfors; Yantao Li (Algal Research, 2026)

Culture performance and physiology of triploid eastern oysters (Crassostrea virginica) in their northern range - Thomas Kiffney; Romain Lavaud; Paul Rawson; Gary H. Wikfors; Damian C. Brady (Aquaculture, 2025)

Correction: Refining the Farm Aquaculture Resource Management Model for Shellfish Nitrogen Removal at the Local Scale - Skylar R. Bayer; Alhambra M. Cubillo; Julie M. Rose; Joao G. Ferreira; Mark Dixon; Annita Alvarado; Janine Barr; Genevieve Bernatchez; Shannon Meseck; Matthew Poach; Emilien Pousse; Gary H. Wikfors; et al. (Estuaries and Coasts, 2024)

Refining the Farm Aquaculture Resource Management Model for Shellfish Nitrogen Removal at the Local Scale - Skylar R. Bayer; Alhambra M. Cubillo; Julie M. Rose; Joao G. Ferreira; Mark Dixon; Annita Alvarado; Janine Barr; Genevieve Bernatchez; Shannon Meseck; Matthew Poach; Emilien Pousse; Gary H. Wikfors; et al. (Estuaries and Coasts, 2024)
Nutrient-related environmental degradation in coastal waters is a continuing global problem. Bivalve shellfish farms show nutrient removal capabilities similar to some traditional management strategies and in some places have been incorporated into nutrient management programs to help achieve water quality goals. Bioextractive nutrient removal varies by farmed species and is influenced by environment parameters; thus, data and information for both are needed to estimate nutrient mitigation potential of shellfish farms. The Farm Aquaculture Resource Management (FARM) model, calibrated for farmed species, uses local environmental and farming practice data to simulate interactions between the farmed population and the local environment and to optimize cultivation practices for economic gain. We calibrated the model to predict nitrogen removal by Eastern oyster ( Crassostrea virginica ) farms with specific field and experimental data on oysters, their local environment, and farm practices in Long Island Sound, CT, USA. Previous FARM applications were not validated for nitrogen removal with local data. In the harvest when ready (HWR) model scenario (oysters are harvested when they reach harvest size), the farm removed 159 kg N ha −1 year −1 while the non-HWR scenario (all oysters are harvested at one time) removed 274 kg N ha −1 year −1 . These estimates are within the range of previously reported in-water bioextraction studies in the Northeastern USA. The robust outputs from this validated model can be reliably used in marine spatial planning efforts and by nutrient managers to predict the nitrogen removal benefits that could be achieved through new or expanded eastern oyster farms in eutrophic environments.

Properties and Behavior of Sexual Life Stages Underlying Dinoflagellate HAB Events of Cyst-Producing Species That Disrupt Fisheries and Aquaculture - Agneta Persson; Barry C. Smith; Jennifer H. Alix; Gary H. Wikfors (Reviews in Fisheries Science & Aquaculture, 2024)

Metabolomics and lipidomics reveal the effects of the toxic dinoflagellate Alexandrium catenella on immune cells of the blue mussel, Mytilus edulis - Stéphane Beauclercq; Olivier Grenier; Alexandre A. Arnold; Dror E. Warschawski; Gary H. Wikfors; Bertrand Genard; Réjean Tremblay; Isabelle Marcotte (Harmful Algae, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Biodegradable, metal-chelating compounds as alternatives to EDTA for cultivation of marine microalgae - Justine Sauvage; Gary H. Wikfors; Koen Sabbe; Nancy Nevejan; Steven Goderis; Philippe Claeys; Xiaoxu Li; Alyssa Joyce (Journal of Applied Phycology, 2021)
Iron (Fe) is an essential nutrient for microalgal metabolism. The low solubility of Fe in oxic aquatic environments can be a growth-limiting factor for phytoplankton. Synthetic chelating agents, such as ethylenediaminetetraacetic acid (EDTA), are used widely to maintain Fe in solution for microalgal cultivation. The non-biodegradable nature of EDTA, combined with sub-optimal bioavailability of Fe-EDTA complexes to microalgae, indicates opportunity to improve microalgal cultivation practices that amplify production efficiency and environmental compatibility. In the present study, the effects of four organic chelating ligands known to form readily bioavailable organic complexes with Fe in natural aquatic environments were investigated in relation to growth and biochemical composition of two marine microalgae grown as live feeds in shellfish hatcheries ( Chaetoceros calcitrans and Tisochrysis lutea ). Three saccharides, alginic acid (ALG), glucuronic acid (GLU), and dextran (DEX), as well as the siderophore desferrioxamine B (DFB), were compared to EDTA. Organic ligands characterized by weaker binding capacity for cationic metals (i.e., ALG, GLU, DEX) significantly improved microalgal growth and yields in laboratory-scale static batch cultures or bubbled photobioreactors. Maximal microalgal growth enhancement relative to the control (e.g., EDTA) was recorded for GLU, followed by ALG, with 20–35% increase in specific growth rate in the early stages of culture development of C. calcitrans and T. lutea . Substitution of EDTA with GLU resulted in a 27% increase in cellular omega 3-polyunsaturetd fatty acid content of C. calcitrans and doubled final cell yields. Enhanced microalgal culture performance is likely associated with increased intracellular Fe uptake efficiency combined with heterotrophic growth stimulated by the organic ligands. Based upon these results, we propose that replacement of EDTA with one of these organic metal-chelating ligands is an effective and easily implementable strategy to enhance the environmental compatibility of microalgal cultivation practices while also maximizing algal growth and enhancing the nutritional quality of marine microalgal species commonly cultured for live-feed applications in aquaculture.

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA - Suzanne B. Bricker; Raymond E. Grizzle; Philip Trowbridge; Julie M. Rose; Joao G. Ferreira; Katharine Wellman; Changbo Zhu; Eve Galimany; Gary H. Wikfors; Camille Saurel; Robin Landeck Miller; James Wands; et al. (Estuaries and Coasts, 2020)
Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster ( Crassostrea virginica ) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-scale ecological model was not available. Farm-scale N removal results (0.072 metric tons acre −1 year −1 ) were up-scaled to provide a system-wide removal estimate for current (0.61 metric tons year −1 ), and potential removal (2.35 metric tons year −1 ) at maximum possible expansion of licensed aquaculture areas. Restored reef N removal was included to provide a more complete picture. Nitrogen removal through reef sequestration was ~ 3 times that of aquaculture. Estimated reef-associated denitrification, based on previously reported rates, removed 0.19 metric tons N year −1 . When all oyster processes (aquaculture and reefs) were included, N removal was 0.33% and 0.54% of incoming N for current and expanded acres, respectively. An avoided cost approach, with wastewater treatment as the alternative management measure, was used to estimate the value of the N removed. The maximum economic value for aquaculture-based removal was $105,000 and $405,000 for current and expanded oyster areas, respectively. Combined aquaculture and reef restoration is suggested to maximize N reduction capacity while limiting use conflicts. Comparison of removal based on per oyster N content suggests much lower removal rates than model results, but model harvest estimates are similar to reported harvest. Though results are specific to GBP, the approach is transferable to estuaries that support bivalve aquaculture but do not have complex system-scale hydrodynamic or ecological models.

Application of Environmental DNA Metabarcoding to Spatiotemporal Finfish Community Assessment in a Temperate Embayment - Yuan Liu; Gary H. Wikfors; Julie M. Rose; Richard S. McBride; Lisa M. Milke; Renee Mercaldo-Allen (Frontiers in Marine Science, 2019)

Depth Selection and In Situ Validation for Offshore Mussel Aquaculture in Northeast United States Federal Waters - Darien Danielle Mizuta; Gary H. Wikfors (Journal of Marine Science and Engineering, 2019)
As mariculture progresses offshore in the US Exclusive Economic Zone, technical and ecological challenges need to be overcome, such as the choice of suitable sites that favor the production of target species. The offshore culture of blue mussels, Mytilus edulis, is performed with submerged longlines and mussels need to withstand more motion than on coastal sites. Temperature affects the ability of the byssus to adhere to farming rope, while chlorophyll concentration provides an estimation of food availability. Together, these are important factors in predicting the suitability of offshore mussel farms. To identify suitable depth of submersion for mussel ropes in New England federal waters, historical oceanographic data of temperature and chlorophyll a from 2005 to 2012 were used. The results suggest that mussel ropes were submerged during summer to a minimum depth of 15 m in northern and a 20-m depth in southern areas of New England where temperature is at a species-optimum and phytoplankton biomass is abundant. For the site offshore Massachusetts, in situ biodeposition measurements validated predicted depth, confirming satisfactory mussel performance. Promising local areas have shallow thermoclines, such as offshore Long Island, Cape Ann and New Hampshire. Recommended depths can be adjusted to future temperature increases associated with climate change.

Seeking the perfect oyster shell: a brief review of current knowledge - Darien Danielle Mizuta; Gary H. Wikfors (Reviews in Aquaculture, 2019)
Current trends in the seafood market indicate increased demand for within‐shell oysters, associated with increasing popularity of oyster bars. As this specialized, demanding market increases globally, there is strong incentive to improve quality. In this context, the manipulation of oyster shell traits through aquaculture as a means of improving oyster quality is timely and promising in terms of marketing. Several oyster shell characteristics, most especially shape, measured as length (L), width (W) and depth (D), result from a combination of three factors: genetics, environmental condition to which the oyster is exposed and husbandry practices. Although breeding programmes have targeted several important commercial traits, selection for shell traits has not been widely performed. Additionally, accumulated knowledge of the effects of environmental conditions and farming methods on shell characteristics exists at a local level, but as such, it is not always validated with scientific data. The existing local knowledge and practices, however, are of extreme importance for the improvement and adaptation of the farming sector to market demands. Current knowledge about the genetic, environmental and husbandry effects on shell and related aquaculture practices for manipulation of shell appearance and robustness in commercially important oysters of the Genus Crassostrea is compiled here. As the topic has not been well documented in the academic field, information from scientific articles was complemented by technical reports and commercial sources. A combination of aquaculture practices is needed to produce oysters of acceptable shape, thickness, cleanliness and colour, although suitable shell characteristics may vary with different markets.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Modeling food choice in the two suspension-feeding bivalves, Crassostrea virginica and Mytilus edulis - Emmanuelle Pales Espinosa; Robert M. Cerrato; Gary H. Wikfors; Bassem Allam (Marine Biology, 2016)

Silicon Deficiency Induces Alkaline Phosphatase Enzyme Activity in Cultures of Four Marine Diatoms - Soledad Fuentes; Gary H. Wikfors; Shannon Meseck (Estuaries and Coasts, 2014)

Quantifying Feeding Behavior of Ribbed Mussels (Geukensia demissa) in Two Urban Sites (Long Island Sound, USA) with Different Seston Characteristics - Eve Galimany; Julie M. Rose; Mark S. Dixon; Gary H. Wikfors (Estuaries and Coasts, 2013)

Short communication: adaptability of the feeding behavior of intertidal ribbed mussels (Geukensia demissa) to constant submersion - Eve Galimany; Jennifer H. Alix; Mark S. Dixon; Gary H. Wikfors (Aquaculture International, 2013)

Immune response and mechanical stress susceptibility in diseased oysters, Crassostrea virginica - Steven B. Roberts; Inke Sunila; Gary H. Wikfors (Journal of Comparative Physiology B, 2012)

Differences in the Soluble, Residual Phosphate Concentrations at Which Coastal Phytoplankton Species Up-regulate Alkaline-Phosphatase Expression, as Measured By Flow-Cytometric Detection of ELF-97® Fluorescence - Shannon L. Meseck; Jennifer H. Alix; Gary H. Wikfors; J. Evan Ward (Estuaries and Coasts, 2009)

Toxic dinoflagellates (Alexandrium fundyense and A. catenella) have minimal apparent effects on oyster hemocytes - Hélène Hégaret; Gary H. Wikfors; Philippe Soudant; Christophe Lambert; Sandra E. Shumway; Jean Baptiste Bérard; Patrick Lassus (Marine Biology, 2007)

Nutrient interactions between phytoplankton and bacterioplankton under different carbon dioxide regimes - Shannon L. Meseck; Barry C. Smith; Gary H. Wikfors; Jennifer H. Alix; Diane Kapareiko (Journal of Applied Phycology, 2007)